Hypoxia-Inducible Factor-1α Regulates High Phosphate-Induced Vascular Calcification via Type III Sodium-Dependent Phosphate Cotransporter 1 - Chengkun Guo; Zhengli Quan; Jingjing Ke; Hualong Zang; Qiuping Teng; Xin Li; Dan Peng; Ping Wang (Cardiology Research and Practice)
Vascular calcification (VC) has a high incidence in patients with chronic kidney disease, which is a worldwide public health problem and presents a heavy burden to society. Hypoxia-inducible factor (HIF)-1α, the active subunit of HIF-1, has been reported to play a vital role in high phosphate-induced VC. However, the underlying mechanism is still undetermined, and effective treatment is unavailable. In the present study, human aortic smooth muscle cells (HASMCs) were cultured under normal or high phosphate media conditions. HIF-1α small interfering RNA and overexpression plasmids were employed to regulate HIF-1α expression. Phosphonoformic acid was employed to restrain the function of type III sodium-dependent phosphate cotransporter 1 (Pit-1). The expression levels of HIF-1α, Pit-1, runt-related transcription factor 2 (Runx2), and smooth muscle 22 alpha (SM22α) were evaluated, and the calcium contents were also examined. Cell growth was assessed using an MTT assay. High phosphate stimulation caused an upregulation in HIF-1α and Pit-1 expression levels and induced calcium depositions in HASMCs. Upregulation of Runx2 expression accompanied by downregulation of SM22α expression was observed in the high phosphate group. Following the suppression of HIF-1α expression, there was a concomitant attenuation in Pit-1 expression, calcium deposition, the alteration of phenotypic transition marker genes, and vice versa. The most serious calcium deposition was noted in HASMCs cultured under high phosphate conditions which were pretreated with a HIF-1α overexpression plasmid. However, when the biological functions of Pit-1 were restrained, the putative serious calcium deposition was not formed even in HASMCs transfected with a HIF-1α overexpression plasmid. The findings confirmed that HIF-1α regulated Pit-1 expression and exerted its pro-calcifying effect through Pit-1, which identified HIF-1α and Pit-1 as therapeutic targets for high phosphate-induced VC.